Relationship Pattern Of Formula Milk Using A Milk Bottle To The Risk Of Dental Caries In Children Aged 3-6 Years In Bontorannu Village Bulukumba Regency - Nurnainah Nurnainah; Asneni Palembai; Sri Wahyuni Bahrum; Suciani Suciani; Andryana Agrevita (CV. Inara, 2021)
WHO’s data in 2017 shows that 60-90% of children’s in industrilized countries experience dental caries. Whereas in Indonesia, especially in South Sulawesi, based on a survey conducted by the Hasanuddin University Faculty of Dental Health in 2019 showed that children’s suffering from dental caries reached up to 90.05%. The purpose of this research is to determine the relationship between the pattern of formula milk using milk bottles against the risk of dental caries in children. Type of the research is quantitative study with an observational method using a cross sectional approach. Population in this study were all children’s aged 3-6 years in Bontorannu Village, Bulukumba Regency who consumed formula milk using a milk bottle, as many 38 children’s. Sampling was done by nonprobability sampling with a total sampling technique. Research result shows that children who consume formula milk using milk bottles correctly as many 13 (34.2%) isn’t risk suffering of dental caries, and wrong as many 25 (65.8%) is risk suffering dental caries. The results of data analysis using the chi-square test obtained p value=0.000 (0.05), H0 is rejected or there is a significant relationship between the pattern of formula milk using milk bottles and risk dental caries in children’s.